Os que querem, os que podem e os que têm: um estudo sobre as forças motrizes da proliferação de armamentos nucleares e mísseis balísticos - Oliveira, Raquel de Bessa Gontijo de (2018)
Nuclear weapons proliferation represents a yet unsolved problem in the international security agenda, and it is intimately related to ballistic missile proliferation. Specialized literature on this topic contains different hypotheses about what causes proliferation, which can be distinguished between those that refer to states’ demand for these weapons, and those that emphasize the role of supply, represented by states’ access to sensitive technology through international civil cooperation. In this research, we investigate the role that different factors play in influencing states’ decision to acquire or relinquish nuclear weapons and ballistic missiles, and we contrapose forces related to demand and supply. Through a quantitative analysis, we identify some relevant correlations, among which the relevance of insecurity as a driving force of proliferation and the apparent irrelevance of access to technology through international cooperation are particularly noteworthy. From our statistical analysis, we select the case of Canadian non-acquisition to be the object of more detained investigation, through which we confirmed the importance of the security context and the marginal role of access to technology, besides identifying an influence of identity aspects on the non-acquisition policy. In light of this, we conclude that factors relating to demand have a far larger impact on proliferation than factors relating to supply